Iodide Residues in Milk Vary between Iodine‐Based Teat Disinfectants. Issue 7 (3rd June 2016) - French, Elizabeth A.; Mukai, Motoko; Zurakowski, Michael; Rauch, Bradley; Gioia, Gloria; Hillebrandt, Joseph R.; Henderson, Mark; Schukken, Ynte H.; Hemling, Thomas C.
Abstract: Majority of iodine found in dairy milk comes from the diet and teat disinfection products used during milking process. The objective of this study was to evaluate the effects of 4 iodine‐based teat dips on milk iodide concentrations varying in iodine level (0.25% vs. 0.5%, w/w), normal low viscosity dip versus barrier dip, and application method (dip vs. spray) to ensure safe iodine levels in dairy milk when these products are used. The iodine exposure study was performed during a 2‐wk period. The trial farm was purged of all iodine‐based disinfection products for 21 d during a prestudy "washout period, " which resulted in baseline milk iodide range of 145 to 182 ppb. During the experiment, iodine‐based teat dips were used as post‐milking teat disinfectants and compared to a non‐iodine control disinfectant. Milk iodide residue levels for each treatment was evaluated from composited group samples. Introduction of different iodine‐based teat disinfectants increased iodide residue content in milk relative to the control by between 8 and 29 μg/L when averaged across the full trial period. However, residues levels for any treatment remained well below the consumable limit of 500 μg/L. The 0.5% iodine disinfectant increased milk iodide levels by 20 μg/L more compared to the 0.25% iodine. Compared to dip‐cup application, spray application significantly increased milk iodide residue by 21 μg/L and utilized approximately 23% more teat dip. This carefully controlled study demonstrated an increase in milk iodide concentrations from iodine disinfectants, but increases were small and within acceptable limits.